Enhancing the employability of development in planning and management graduates, University of Limpopo - Lebotsa, Khutso Piet (My University, 2024)
Higher Education Institutions (HEIs) graduates face high unemployment levels. This is largely ascribable to the absence of opportunities and or their lack of employability skills and abilities needed in the corporate world. Like other graduates across various fields of study in South Africa, Development Planning and Management graduates from the University of Limpopo are confronted with difficulties of transiting to the labour market. Several factors contribute to these difficulties, common among them being the lack of work-integrated learning, poor marketing of qualifications, and poor collaboration between the universities and the corporate sector. Against this backdrop, this study sought to enhance the employability of Development in Planning and Management graduates in the University of Limpopo, relying on these graduates as a case study data collection and an evaluation of the factors that contribute to the non-employability of graduates in lieu of the needs of the labour market. This study aimed to investigate the employability of graduates from the University of Limpopo. A normative and evaluation research design was used in the study. For primary and secondary data collection, the study used questionnaires, interview schedules, and a literature review. The study included 49 participants and 4 key informants. It was found that the integration of work-integrated learning into the university curriculum, proper marketing of the degree programme, and collaborative efforts between HEIs and the corporate sector can enhance the employability of Development in Planning and Management graduates. In conclusion, the study highlights that HEIs must incorporate work-integrated learning into curricula and establish collaborative efforts between HEIs and the labour market, in order to effectively respond to the evolution of attributes and abilities that the economy and corporate world demand. Therefore, the study recommends that universities must align their degree programmes with the demands of the corporate world, strengthen collaborations with the corporate sector, promote work-integrated learning, and involve the corporate sector in curriculum designs and reviews to assure that university curriculum respond to the expectations of the corporate world.
Thesis (M. Dev. (Planning and Management)) -- University of Limpopo, 2024
Keywords: Graduate employability; Unemployment; Graduates; Corporate sector; College graduates; Employability; College graduates -- Employment; Education, Higher -- South Africa